2009
DOI: 10.1007/s10255-008-8823-1
|View full text |Cite
|
Sign up to set email alerts
|

A single-server discrete-time retrial G-queue with server breakdowns and repairs

Abstract: This paper concerns a discrete-time Geo/Geo/1 retrial queue with both positive and negative customers where the server is subject to breakdowns and repairs due to negative arrivals. The arrival of a negative customer causes one positive customer to be killed if any is present, and simultaneously breaks the server down. The server is sent to repair immediately and after repair it is as good as new. The negative customer also causes the server breakdown if the server is found idle, but has no effect on the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…where we also use Equation (19). Since z * = 1 and under the assumption that z * = 0, the probability P(0, 0) then directly follows from (20) as…”
Section: System Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…where we also use Equation (19). Since z * = 1 and under the assumption that z * = 0, the probability P(0, 0) then directly follows from (20) as…”
Section: System Contentmentioning
confidence: 99%
“…For related work on discrete-time G-queues with negative customers, the reader is referred to [3,7,14,[16][17][18][19][20][21][22][23]. For work on continuous-time queueing models with negative customers and/or disasters, we refer to the bibliography in [24,25] and the more recent papers [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Zhang et al [18] studied the noncooperative and cooperative strategies of customers in the context of a retrial queueing model where the server is subject to vacations, breakdowns and repairs. However, although more attention has been paid on the analysis of discrete time queueing models with unreliable server, such as Atencia and Moreno [1], Bruneel [2], Fiems et al [5][6], Moreno [9], Morozov et al [10], Vinck and Bruneel [14], Wang and Zhang [16][17], among others, it is found that there is no work concerning the equilibrium balking behavior in the discrete-time queues with server breakdowns and repairs.…”
Section: Introductionmentioning
confidence: 96%
“…Queue with negative arrivals called G-queue was first introduced by Gelenbe [4] with a view to modeling neural networks. Wang and Zhang [9] considered a discrete time retrial queue with negative arrivals. Peng et al [7] suggested an M/G/1 retrial G-queue with pre-emptive resume priority and collisions under linear retrial policy.…”
Section: Introductionmentioning
confidence: 99%